The Respons on Growth of Acacia mangium Willd. by Using Dolomit and HSC (Humic Substances Complex) on Ex Coal Mineland RESPON PERTUMBUHAN Acacia mangium WILLD. TERHADAP PENAMBAHAN KAPUR DAN HSC (HUMIC SUBSTANCES COMPLEX) PADA LAHAN PASCA TAMBANG BATUBARA - Nuri Jelma Megawati; Basuki Wasis; Yadi Setiadi (Jurnal Silvikultur Tropika, 2014)
The success rate of revegetation on ex-coal mineland is low. It is caused by the characteristic of soil that can’t support the plant growth. The objective of this research were to study the characteristic of soil in various type of A. mangium growth condition as well as the efforts for soil amandement with dolomit and Humic Substances Complex to improve soil condition and A. mangium growth on ex-coal mineland. Soil analysis was conducted in three condition of A. mangium growth. Those are normal, moderate and low. This research was conducted in the low growth of A. mangium with two factor (dolomit and Humic Substances Complex) and 16 repetition. Design research was Split Block Design. The Result showed that normal growth of A. mangium has been supported by physical, chemical and biological soil condition. The main factor of moderate and low growth of A. mangium were low pH and high Al soluble. Combination treatment dolomit and HSC have given significant influence on height of A. mangium on 3rd location. Dolomit treatment on A. mangium has given significant influence on height of A. mangium on all location. HSC treatment isn’t yet significant influence ongrowing A. mangium.Keywords : A. mangium, dolomit, ex-coal mineland, HSC, soil analysis